Carotenoids production from red yeasts using waste glycerol as a sole carbon source - A. Manowattana (2018)
Fourteen strains of red yeasts from a culture collection Thailand Institute Scientific and Technological Research (TISTR) were screened for carotenoids production using yeast maltextract medium (YM), basal medium supplemented with either pure glycerol (BMP) or waste glycerol (BMW) as a sole carbon source. The results revealed that eleven strains of the red yeasts could grow and produced carotenoids in YM and BMP but only nine strains were observed in BMW. Sporobolomyces pararoseus TISTR5213 showed the maximum total carotenoids content of 912.74, 845.52 and 948.34 μg (g DCW)-1 in YM, BMP and BMW, respectively. The optimal conditions for carotenoids production in BMW by S. pararoseus TISTR5213 were; 20 g L-1 waste glycerol, 1.0 g L-1 yeast extract, 5.3 g L-1 (NH4)2SO4, 5.5 g L-1 KH2PO4, 3.7 g L-1 K2HPO4, 0.5 g L-1, MgSO4.7H2O, 0.2 g L-1 MnSO4.H2O and 0.25 g L-1 NaCl with an initial pH of 6.0 and agitation speed of 200 rpm at 25°C for 5 days. Under the optimized conditions, the maximum total carotenoids content of 1,058.42 μg (g DCW)-1 was achieved. In comparison, the cost of carotenoids production in YM, BMG and BMW were 0.177, 0.043 and 0.025 Baht (μg carotenoids)-1 (g medium)-1, respectively. These results indicated that waste glycerol showed high potential as a carbon source for carotenoids production.